ТҮРКИЙ ТИЛ БИЛИМИНДЕ ФОЛЬКЛОРОНИМЛЕРДИҢ ИЗЕРТЛЕНИЎИ - Абдиназимов, Ш.; Толыбаев, Х. (FAN va JAMIYAT, 2018)
In the article, the information about onomastics units of folklore language in the study of Turkic languages is given. There has been done the investigation analysis in the toponymic and anthroponymic study of different genres of folklore.